Desenvolvimento e caracterização de filmes de polissacarídeos extraídos de borra de café. - Michelle Jennifer Pereira de Azevedo Batista (2023)
Most polymeric materials are synthetic and derived from petroleum, hence they accumulate in landfills or follow the flow of the hydrological cycle, accumulating in the ocean. Researchers have been studying alternatives to replace polymeric materials that come from petroleum, which take years to degrade. Wastes from agroindustry are discarded on a large scale annually and they are rich in organic compounds such as polysaccharides, which could be used as polymers to produce films. Spent coffee grounds (SCG) are rich in polysaccharides and other organic compounds as well. Around 6,5 million tons of SCG are generated every year, and it is an environmental problem around the world, including Brazil, which is the second largest coffee consumer and the largest coffee grounds producer in the world. Given the aforementioned, it was the aim of this work the development of films from spent coffee grounds, which are rich in cellulose, galactomannans and arabinogalactans. Thus, SCG were treated by a solution with 35% (v/v) alkaline hydrogen peroxide. The insoluble material showed 63% polysaccharides and yield 56 %, whereas SCG exhibited 46%. For the development of films, SCG were dissolved in 67% zinc chloride solution and a film was produced using the phase inversion technique by immersion precipitation. Then, two types of crosslinking were performed, the first forming chemical interaction between ions and polysaccharides by calcium chloride and the second was performed through covalent bonds with 1,4-phenylenediboronic acid. The films with Ca2+ ions exhibited a greater barrier to water vapor and greater tensile strength than the control film and the films with 1,4-phenylenediboronic acid, which showed a high moisture content, greater permeability to water vapor and a higher percentage of elongation. Furthermore, because of the knowledge about of degradation on the polysaccharides due to the use of zinc chloride solution to dissolve the SCG, the present work evaluated the effects of the ZnCl2 solution on the cellulose, galactomannans, and arabinogalactans of the SCG matrix. We tested alternatives to minimize it through the addition of lower concentrations of ZnCl2 (53, 60 and 67%) assisted by ultrasound. The materials dissolved with 53% ZnCl2 showed greater thermal stability with a peak in the DTG (derivative thermogravimetry) located at a higher temperature than the other samples. The results are promising, and it is suggested as future research the development of films from these materials.